ANALISIS PERPUTARAN PIUTANG, PIUTANG RATA-RATA DAN RASIO PIUTANG ATAS PENDAPATAN TERHADAP PROFITABILITAS PADA PDAM TIRTA BUMI SENTOSA KABUPATEN KEBUMEN - Marlini, Wenny; Widya Utami, Mega (Politeknik Dharma Patria Kebumen, 2019)
To determine the effectiveness of the management of accounts receivable, one of them by looking at the management of accounts receivable that is by calculating receivables turnover, average accounts receivable and the ratio of revenue. The calculation aims to determine how the performance of its receivables management. PDAM to manage accounts still less than optimal seen from the accounts receivable turnover decreased means that the longer the company's capital back into cash, average accounts receivable increase means the greater the greater the age of accounts receivable collectibility of accounts receivable and ratio of receivables from increased revenues and reduced income when receivables increase.  The solution is to give the author PDAM must control receivables and anticipate the existence of doubtful receivables, then the company needs to provide policies in collection of accounts receivable which the company hopes that customers deposit the payment on time. Results calculation accounts receivable turnover in 2012 was amounted to 5,7 times, and in 2013 was amounted to 5.3 times the mean decreases, average accounts receivable in 2012 was amounted 63 days and in 2013 was amounted to 69 days means increased, and the ratio of receivables on income in 2012 was amounted to 0.1744% and in 2013 was amounted to 0.1888% mean increase. Receivables increased revenue decreased. Results of analysis of receivables turnover PDAM Tirta Bumi Sentosa Kabupaten Kebumen not good, average receivables including unfavorable, and the ratio of receivables on income analysis results are less good too. It can be concluded that the receivables on PDAM Tirta Bumi Sentosa Kabupaten Kebumen not good.